Identification of Sex-Related Genes from the Three-Spot Swimming Crab Portunus sanguinolentus and Comparative Analysis with the Crucifix Crab Charybdis feriatus - Yin Zhang; Khor Waiho; Mhd Ikhwanuddin; Hongyu Ma (Animals, 2021)
Crabs within the family Portunidae are important marine species in both aquaculture and fishery sectors. The current aquaculture status of most portunids, however, still relies on wild-caught fisheries due to the lack of essential knowledge regarding their reproductive biology and underlying governing mechanism. With the advancement of sequencing technology, transcriptome sequencing has been progressively used to understand various physiological processes, especially on non-model organisms. In the present study, we compared the differentially expressed genes (DEGs) between sexes of Portunus sanguinolentus based on their gonadal transcriptome profiles and subsequently contrasted them with the gonadal DEGs of Charybdis feriatus, the other member of Family Portunidae. In total, 40,964 DEGs between ovaries and testes were uncovered, with 27,578 up- and 13,386 down-regulated in females. Among those, some sex-related DEGs were identified, including a dmrt-like (DMRT) gene which was specifically expressed in males. C. feriatus has approximately 63.5% of genes common with P. sanguinolentus, with 62.6% showing similar expression patterns. Interestingly, the DMRT gene was specifically expressed in male P. sanguinolentus while its homologous gene—doublesex (DSX)—was specifically expressed in male C. feriatus. The DEGs obtained from the gonadal transcriptome of P. sanguinolentus are a beneficial resource for future genetic and genomic research in P. sanguinolentus and its close species. The transcriptomic comparison analysis might provide references for better understanding the sex determination and differentiation mechanisms among portunids.